2000
DOI: 10.1209/epl/i2000-00445-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic tunnel junctions with single-crystal electrodes: A crystal anisotropy of tunnel magneto-resistance

Abstract: A strong dependence of tunnel magnetoresistance (TMR) on the crystal orientation of ferromagnetic electrodes was confirmed experimentally. We studied the TMR of Fe/Al2O3/Fe50Co50 tunnel junctions with single-crystal Fe electrodes of different crystal orientations and found that the TMR ratio increased from 13% to 42% at 2K (8% to 26% at room temperature) when the crystal orientation was changed from (100) to (211). Such a TMR anisotropy could be explained in terms of the anisotropic spin polarization of Fe bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…Although some preliminary effort was undertaken to study the role of the band structure of ferromagnetic films in tunneling [2], no definitive observations were made till the advent of tunnel magnetoresistance (TMR) in magnetic tunnel junctions (MTJs). Then, Yuasa et al [3] and LeClair et al [4] experimentally demonstrated the influence of epitaxial Fe and textured Co films on TMR and tunneling conductance, respectively. Regarding the nature of the electronic wave functions that govern the tunneling probability through AlO x , the dominance of the spherically symmetric s-like electrons has been experimentally demonstrated [5,6].…”
mentioning
confidence: 99%
“…Although some preliminary effort was undertaken to study the role of the band structure of ferromagnetic films in tunneling [2], no definitive observations were made till the advent of tunnel magnetoresistance (TMR) in magnetic tunnel junctions (MTJs). Then, Yuasa et al [3] and LeClair et al [4] experimentally demonstrated the influence of epitaxial Fe and textured Co films on TMR and tunneling conductance, respectively. Regarding the nature of the electronic wave functions that govern the tunneling probability through AlO x , the dominance of the spherically symmetric s-like electrons has been experimentally demonstrated [5,6].…”
mentioning
confidence: 99%
“…A single-band approach is sufficient to model the TMR in amorphous sputtered MTJs 28 and can satisfactorily describe the TMR n and V out of epitaxial singleand double-barrier FeCoB/MgO junctions. 29 In our case we have to go beyond parabolic dispersions and the single-band 30 In our calculations for metals the effective mass is equal to the free-electron mass. Figure 4 presents the TMR as function of the bias for different lattice parameters, showing that the TMR, in general, behaves nonmonotonically.…”
Section: Tunnel Magnetoresistance Under Strainmentioning
confidence: 99%
“…Transmission electron microscopy ͑TEM͒ and grazing incidence x-ray reflectivity ͑GIXR͒ are powerful tools for thin films thickness determination, but the visualized area for TEM may not be representative of the effective junction area as a whole. 15,16 On the other hand, GIXR determines an average thickness over relatively large areas. In junctions with fluctuations of thickness and/or barrier composition, the tunnel current concentrates in small parts of the junction area, [17][18][19] designated hot spots, where the barrier thickness and/or height achieve its lowest value.…”
Section: Introductionmentioning
confidence: 99%